Avaliação de vacinas contra brucelose bovina no Brasil - Karina Leite Miranda (2009)
The present work aimed to study the vaccines approved by the PNCEBT in Brazil. The first objective was to evaluate the growth of B. abortus strains on media containing different inhibitor agents in order to differentiate the vaccine strains S19 and RB51 from challenge strains and other field isolates, concluding that rifampicin, erythritol and thionin are good inhibitor agents. The second aim was to evaluate different strains of mice (CD-1, BALB-c and Swiss), and challenge strains (544 and 2308), in the immunogenicity tests of S19 and RB51 vaccines. This experiment demonstrated that both challenge strains can be used in immunogenicity tests of S19 and RB51, as well as the three strains of mice; however the use of BALB-c requires more studies. The third study aimed to compare the biological properties (immunogenicity and residual virulence) and genotypic profile of eight S19 vaccines commercialized in Brazil with the reference S19 (USDA). This study comproved that all S19 vaccines commercialized in Brazil show adequate biological properties when compared to the reference vaccine strain. The last goal of this study was to evaluate the shedding of B. abortus in the milk of cows vaccinated with RB51. The milk of vaccinated animals was tested by culture and PCR up to 63 days after vaccination and only one sample of milk was positive in PCR, on the first day after vaccination. Thus, the spread of RB51 by milk seems not to be a public health problem, but pasteurization of the milk is highly recommended. In conclusion, Brazil has great tools to control brucellosis